2005
DOI: 10.1242/jcs.02624
|View full text |Cite
|
Sign up to set email alerts
|

Differential contributions of connexin37 and connexin43 to oogenesis revealed in chimeric reaggregated mouse ovaries

Abstract: The gap junction proteins connexin37 and connexin43 are required for ovarian folliculogenesis in the mouse. To define their respective roles in oogenesis, chimeric ovaries containing either null mutant oocytes and wild-type granulosa cells or the reverse combination were grafted to the renal capsules of immunodeficient female mice. After three weeks, the oocytes were tested for meiotic competence and fertilizability in vitro. Ovaries composed of connexin43-deficient oocytes and wild-type granulosa cells produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 25 publications
4
82
1
2
Order By: Relevance
“…The significant localisation of Cx43 in the zona pellucida before IVM may be associated with an increased activity of gap junction transport in not fully grown oocytes which did not reach the MII stage. Contrary to these results, Gittens and Kidder (2005) found that another connexin, Cx37, is involved in the formation of fully competent gametes and has a more important function than Cx43. They have shown that mouse COCs do not need Cx43 to grow to developmentally competent cells, but Cx37 seems to be necessary for proper communication between surrounding cumulus-granulosa cells and oocytes during normal oogenesis.…”
Section: A B C Dcontrasting
confidence: 87%
“…The significant localisation of Cx43 in the zona pellucida before IVM may be associated with an increased activity of gap junction transport in not fully grown oocytes which did not reach the MII stage. Contrary to these results, Gittens and Kidder (2005) found that another connexin, Cx37, is involved in the formation of fully competent gametes and has a more important function than Cx43. They have shown that mouse COCs do not need Cx43 to grow to developmentally competent cells, but Cx37 seems to be necessary for proper communication between surrounding cumulus-granulosa cells and oocytes during normal oogenesis.…”
Section: A B C Dcontrasting
confidence: 87%
“…In the connexin multigene family, connexin 37 is crucial for the establishment of oocyte-granulosa gap junctions, which is important for oocyte development. In connexin 37-knockout mice, oocyte growth ceases at a diameter of 52 m (Carabatsos et al, 2000), and the sole absence of connexin 37 from oocytes is in itself sufficient to compromise both oocyte and follicular development, as has been shown using chimeric ovaries with connexin 37-deficient oocytes and WT granulosa cells (Gittens and Kidder, 2005). Connexin 43 is involved in establishing the gap junctions between granulosa cells, and mouse ovarian follicles lacking connexin 43 are arrested in the early preantral stages (Ackert et al, 2001;Gittens et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…With regard to this, Cx37 is believed to be the only connexin protein supplied from oocytes for the gap junctional channel connecting granulosa cells and oocytes [33]. Supporting this, Gittens and Kidder recently reported using reconstituted chimeric ovaries from Cx37-or Cx43-deficient mice that expression of Cx37 in oocytes, but not granulosa cells, was prerequisite for follicular development [41]. Multiple connexins including Cx43, however, are known to be expressed in granulosa cells [9,10], and the counterpart of Cx37 functioning in the contact region of granulosa cells and oocytes is still unknown.…”
Section: Discussionmentioning
confidence: 94%